Synthesis, characterization, Hirshfeld surface, cytotoxicity, DNA damage and cell cycle arrest studies of N, N-diphenyl-N `-(biphenyl-4-carbonyl/4-chlorobenzoyl) thiocarbamides - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano; Kaur, Manpreet; Jasinski, Jerry P. (Journal of Molecular Structure, 2019)
The condensation reaction of biphenyl-4-carbonyl isothiocyanate/4-chlorobenzoyl isothiocyanate with diphenylamine yielded two new compounds; N-diphenyl-N'-(biphenyl-4-carbonyl) thiocarbamide (1) and N, N-diphenyl-N'-(4-chlorobenzoyl) thiocarbamide (2). Structure of the compounds were determined by analytical, spectroscopic (UV-Visible, FT-IR, H-1, & C-13 NMR), powder and single-crystal X-ray diffraction methods. Hirshfeld surface analysis and their associated two dimensional fingerprint plots of compounds were used as theoretical approach to assess driving force for crystal structure formation via the intermolecular interactions in their crystal lattices. The compounds were screened for their in vitro cytotoxicity activity against a panel of five human cancer cell lines namely; cervical (2008 and C13*) and ovarian carcinoma (A2780, A2780/CP and IGROV-1). Both the compounds exhibited promising activity against cervical and IGROV-1 cancer cells whereas for the other two cell lines appreciable activities were observed. The cell cycle arrest at G(0)/G(1) phase is supported by the DNA damage and apoptosis studies of the compounds against 2008, C13* and IGROV-1 cell lines. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: DNA damage and cell cycle arrest; Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure

Improving the dissolution rate of the anticancer drug dabrafenib - Rai, Sunil K.; Gunnam, Anilkumar; Mannava, M. K. Chaitanya; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Dabrafenib (DBF) is an anticancer drug with selective B-Raf (BRAF) inhibition activity. In 2013, DBF was approved by the U.S. Food and Drug Administration (US-FDA) as a dabrafenib mesylate salt (DBF center dot MS). Because of insolubility in aqueous medium, specifically at the pH 4-8 biorelevant range, DBF is a Biopharmaceutics Classification System (BCS) Class II drug (i.e., low solubility and high permeability). Therefore, screening of novel salts and cocrystals was carried out using Generally Recognized as Safe (GRAS) coformers. A total of 10 salts/cocrystals including the mesylate salt were found to be stable under the crystallization conditions. Among acidic coformers, methane sulfonic acid (MS) and saccharin (SACH) formed salts, while fumaric acid (FA), succinic acid (SA), and adipic acid (ADA) gave cocrystals. However, monoamines formed a monohydrate salt where the water molecule is hydrogen bonded with the aminopyrimidine moiety of DBF. The replacement of monoamines with ethylenediamine (EN) dislocated the water molecule near the free amine of EN in the crystal structure with a change in space group from triclinic (P (1) over bar) to monoclinic (P2(1)/n). Dissolution measurements at pH 1.2 (0.1 N HCl) showed that DBF center dot EN superset of H2O dissolved rapidly compared to the DBF.MS salt (the dissolution rate of DBF center dot EN superset of H2O and DBF center dot MS is 11 and 2 times faster than that of DBF). Structure-activity relationship analysis showed that bonding of the aminopyrimidine moiety with strong hydrogen bond synthons inhibited dissolution, whereas a loosely bound or free site at the aminopyrimidine moiety enhanced the dissolution rate. Finally, a cytotoxicity study was performed for DBF, DBF center dot MS, and DBF center dot EN superset of H2O, which showed that DBF center dot EN superset of H2O is safe for normal cells and yet equally potent against cancer cells. Crystal engineering of an improved formulation of dabrafenib center dot ethylenediamine hydrate is presented as a new anticancer drug.

Salts and cocrystal of etodolac: advantage of solubility, dissolution, and permeability - Rai, Sunil K.; Allu, Suryanarayana; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
{Etodolac (ETD) is a nonsteroidal anti-inflammatory drug (NSAID) approved by the United States Food and Drug Administration (US-FDA) in 1991 for the treatment of rheumatoid arthritis. Because of its poor aqueous solubility and high permeability, ETD falls under Biopharmaceutics Classification System (BCS) Class II drug. The present study was aimed to screen stable salts and cocrystals of ETD using Generally Recognized as Safe (GRAS) and a few non-GRAS coformers. Crystallization of five salts (i.e.

Structural, Hirshfeld surface and in vitro cytotoxicity evaluation of five new N-aryl-N'-alkoxycarbonyl thiocarbamide derivatives - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano (Phosphorus Sulfur and Silicon and the Related Elements, 2020)
Five new compounds, N-(2, 4-dichlorophenyl)-N'-(methoxycarbonyl) thiocarbamide (1), N-(2, 4-dichlorophenyl)-N'-(ethoxycarbonyl) thiocarbamide (2), N-(2, 4-dichlorophenyl)-N'-(2, 2, 2-trichloroethoxycarbonyl) thiocarbamide (3), N-(2,4-dichlrophenyl)-N'-(pentoxycarbonyl) thiocarbamide (4) and N-(4-nitrophenyl)-N'-(pentoxycarbonyl) thiocarbamide (5), have been synthesized by the reaction of various alkoxy chloroformates with 2, 4-dichloroaniline/4-nitroaniline.The molecular structures of the compounds were elucidated by using spectroscopic methods (FT-IR, H-1 and C-13 NMR) and single-crystal X-ray structure analysis of compounds 2 and 5. Antiperiplanar orientation of C = O and C = S group across C-N bonds of thiocarbamide core may be due to the presence of intramolecular (N-H center dot center dot center dot O-C) hydrogen bond in the crystal structure of both the compounds. The presence of intermolecular interactions (C-H center dot center dot center dot S, C-H center dot center dot center dot O and N-H center dot center dot center dot S) in the molecular structure of the compounds has been studied in detail using Hirshfeld surfaces and their associated twodimensional fingerprint plots. In vitro cytotoxicity screening of the synthesized compounds evaluated on a panel of seven human cancer cell lines (cervical carcinoma (2008, C13*), colorectal (HT29 and HCT116) and ovarian carcinoma (A2780, A2780/CP and IGROV-1)) demonstrated significant inhibitory properties.
Keywords: Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure determination

Synthesis, characterisation, Hirshfeld surface and in vitro cytotoxicity evaluation of new N-aryl-N `-Alkoxycarbonyl thiocarbamide derivatives - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano; Kaur, Manpreet; Jasinski, Jerry P. (Journal of Molecular Structure, 2020)
Four new compounds N-(4-nitrophenyl)-N'-(isobutoxycarbonyl) thiocarbamide (1), N-(2, 4-nitrophenyl)-N'-(isobutoxycarbonyl) thiocarbamide (2), N-(4-nitrophenyl)-N'-(ethoxycarbonyl) thiocarbamide (3) and N-(2-Chloro- 4-nitrophenyl)-N'-(ethoxycarbonyl) thiocarbamide (4) were prepared and their structures confirmed by using various spectroscopic (FT-IR, UV-Visible, H-1 and C-13 NMR) and single crystal X-ray studies of 1 and 3. The presence of intramolecular (N-H center dot center dot center dot O=C) hydrogen bond in the crystal structure of both the compounds causes planarity of carbonyl thiocarbamide unit and trans orientation of C=O and C=S group. The intermolecular contacts (C-H center dot center dot center dot S, C-H center dot center dot center dot O and N-H center dot center dot center dot S) present in crystal structures have been examined by Hirshfeld surface analysis and their associated 2D fingerprint plots. All the compounds were assessed for their in vitro cytotoxic properties against a panel of seven human cancer cells such as cervical carcinoma (2008, C13*), colorectal (HT29 and HCT116) and ovarian carcinoma (A2780, A2780/CP and IGROV-1). Among them, compounds 2 and 4 exhibited better activity than 1 and 3 against all the cell lines tested. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure

Entacapone polymorphs: crystal structures, dissolution, permeability, and stability - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Rai, Sunil K.; Suresh, Kuthuru; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
Entacapone (ETP) is a catechol-O-methyltransferase (COMT) drug used to treat Parkinson's disease. ETP is available in the marketplace under the brand name Comtan since 2010, and ETP form-I was first reported in a patent published in 2001. However, analysis of its Xray crystal structures and stability relationship of ETP polymorphs and their dissolution and permeability profile have not yet been reported. We crystallized two new conformational polymorphs of ETP from a water and acetone mixture and studied the structural origin of polymorphism and their phase transformations, stability, equilibrium solubility, dissolution, and permeability properties. The ETP molecule adopts different conformations in the polymorphic structures with slight changes in carbonyl and nitrile group orientations. Thermal analysis suggests that form-III and form-IV are enantiotropically related to form-I, which is the thermodynamically stable form at ambient conditions. In contrast, form-II is monotropically related to form-I. Equilibrium solubility, dissolution, and permeability studies show that form-II persists in the slurry medium and dissolves faster with a high flux rate compared to the stable form-I in phosphate buffer solution at 37 +/- 0.5 degrees C.

Salts, solvates and hydrates of the multi-kinase inhibitor drug pazopanib with hydroxybenzoic acids - Rai, Sunil K.; Baidya, Debjani; Nangia, Ashwini K. (Crystengcomm, 2021)
The marketed formulation of pazopanib (PAZ) suffers from low and variable bioavailability because of its poor dissolution rate and photostability issues. The drug falls under Biopharmaceutics Classification System (BCS) class II of low solubility and good permeability. The hydrogen bonds and supramolecular interactions in crystalline forms of PAZ with hydroxybenzoic acids (HBAs) and dihydroxybenzoic acids (DHBAs), as well as its salts are analyzed. Ten X-ray crystal structures of PAZ which include the reference drug, a tetrahydrofuran solvate (PAZ center dot THF) and eight salts with HBAs/DHBAs are reported. There is proton transfer from the carboxylic group of the coformer acid to the most basic nitrogen atom of the 2-aminopyrimidine ring of PAZ in all cases. Two salts were crystallized in neat form, while the remaining six are solvates and hydrates. The crystal structure of PAZ is stabilized by sulfonamide and 2-aminopyrimidine homosynthons of N-HMIDLINE HORIZONTAL ELLIPSISO and N-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bonds in an R2(2)(8) ring motif. PAZ center dot HBA/DHBA salts consistently contain the aminopyridiniumMIDLINE HORIZONTAL ELLIPSIScarboxylate N+-HMIDLINE HORIZONTAL ELLIPSISO- synthon of the R2(2)(8) ring. The sulfonamide homosynthon of PAZ is disrupted in preference to the formation of N-HMIDLINE HORIZONTAL ELLIPSISO and N-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bonds in salt structures. The presence of an additional basic nitrogen atom in the indazole ring of PAZ promotes hydration and solvation through the O-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bond. Whereas the formation of salts is desirable for pharmaceutical formulation, the inclusion of adventitious solvent and/or water molecules with hydroxybenzoic acid coformers in the cocrystal-salt products is a limitation for this class of coformers. The stability problem faced with hydrates and solvates of PAZ center dot HBA/DHBA salts means that their formation must be carried out by strictly anhydrous procedures. The consistent occurrence of the aminopyridiniumMIDLINE HORIZONTAL ELLIPSIScarboxylate N+-HMIDLINE HORIZONTAL ELLIPSISO- ring synthon is discussed in relation to the previous results of Aakeroy, Nangia and Zaworotko groups on similar acid-base multi-component systems.

Cocrystallization of multi-kinase inhibitor pazopanib with fenamic acids: improving dissolution and inhibiting cell migration - Rai, Sunil K.; Gunnam, Anilkumar; Roy, Debopriya; Rajput, Raveena; Kulkarni, Kiran; Nangia, Ashwini K. (CrystEngComm, 2023)
A multi-kinase inhibitor, pazopanib (PAZ) is cocrystallized with cyclooxygenase (COX) inhibitor fenamic acids to investigate the dissolution rate and inhibition of cell migration in VEGF-triggered HUVEC cells to test the efficacy of stoichiometric drug-drug combinations. Crystallization experiments at the sub-milligram level in an acetonitrile-methanol mixture yielded two drug-drug salt forms of PAZ with flufenamic acid (FFA) and niflumic acid (NFA) as PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named as form I) and PAZ+center dot NFA-. Structures of the crystal forms were characterized by single crystal X-ray diffraction (SC-XRD) method. Crystal structures revealed that the presence of a 2-aminopyrimidine group in PAZ is a strong partner for the carboxyl group in all solid forms, forming an acidMIDLINE HORIZONTAL ELLIPSISpyrimidine heterosynthon with COX inhibitor fenamic acids. To perform dissolution experiments and cell line analysis, the scale-up of both salt forms were done in the acetonitrile-methanol mixture through crystallization, which showed a polymorphic transformation in the case of PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named form II). The thermodynamic stability of PAZ+center dot FFA-center dot ACN (form II) and PAZ+center dot NFA- were analysed using slurry experiment under ambient conditions in pH 1.2 (0.1 N HCl) buffer medium and the residual solid phase was characterized by powder XRD, which showed that PAZ+center dot FFA-center dot ACN (form II) was a metastable solid form while PAZ+center dot NFA- was a stable solid form. The dissolution experiments at gastric pH 1.2 showed that the rate of dissolution of PAZ+center dot FFA-center dot ACN was 10 times higher than PAZ+center dot NFA-. The cell migration assay suggested that PAZ+center dot FFA-center dot ACN inhibited similar to 25% and PAZ+center dot NFA- inhibited similar to 20% migration of HUVEC cells compared to PAZ alone. These investigations suggested that the drug-drug salts PAZ+center dot FFA- and PAZ+center dot NFA- would be potential combo drug candidates for clinical trials. Multi-drug crystalline salts of pazopanib with fenamic acids exhibit enhanced dissolution and 20% higher inhibition in the migration of HUVEC cells compared to the reference drug.

Dabrafenib-panobinostat salt: improving the dissolution rate and inhibition of BRAF melanoma cells - Rai, Sunil K.; Marverti, Gaetano; Gunnam, Anilkumar; Allu, Suryanarayana; Nangia, Ashwini K. (ACS Omega, 2023)
Cocrystallization of the drug-drug salt-cocrystal of the histone deacetylase inhibitor (HDACi) panobinostat (PAN) and b-rapidly accelerated fibrosarcoma (BRAF) inhibitor dabrafenib (DBF) afforded single crystals of a two-drug salt stabilized by N+-H center dot center dot center dot O and N+-H center dot center dot center dot N- hydrogen bonds between the ionized panobinostat ammonium donor and dabrafenib sulfonamide anion acceptor in a 12-member ring motif. A faster dissolution rate for both drugs was achieved through the salt combination compared to the individual drugs in an aqueous acidic medium. The dissolution rate exhibited a peak concentration (Cmax) of approximately 310 mg cm-2 min-1 for PAN and 240 mg cm-2 min-1 for DBF at a Tmax of less than 20 min under gastric pH 1.2 (0.1 N HCl) compared to the pure drug dissolution values of 10 and 80 mg cm-2 min-1, respectively. The novel and fast-dissolving salt DBF-center dot PAN+ was analyzed in BRAFV600E melanoma cells Sk-Mel28. DBF-center dot PAN+ reduced the dose-response from micromolar to nanomolar concentrations and lowered IC50 (21.9 +/- 7.2 nM) by half compared to PAN alone (45.3 +/- 12.0 nM). The enhanced dissolution and lower survival rate of melanoma cells show the potential of novel DBF-center dot PAN+ salt in clinical evaluation.

Polymorph II of hydroxyurea 150 years after its first synthesis - Rai, Sunil K.; Tothadi, Srinu; Arhangelskis, Mihails; George, Christy P.; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2023)
A new polymorph of hydroxyurea (HU) was crystallized 150 years after its first synthesis. Due to its medicinal use in neoplastic diseases and sickle cell anemia, a high throughput screen of HU binary cocrystals was attempted. Instead of a cocrystal, an isoenergetic form II crystallized concomitantly with urea in methanol.